Root and Canal Morphology of Mandibular Premolars in a Saudi Subpopulation: A Cone-Beam Computed Tomography Study - Saad M. Al-Zubaidi; Moazzy I. Almansour; Ahad S. Alshammari; Nada N. Al Mansour; Ahad F. Alshammari; Yazeed S. Altamimi; Ahmed A. Madfa (Hindawi Limited, 2022)
Objectives. The efficacy of root canal therapy is dependent on a thorough understanding of both normal and aberrant root canal morphology. As a result, the purpose of this study was to use CBCT to characterize the exact root and canal morphology of mandibular premolars in a Saudi subpopulation. Methods. The current study included 1000 mandibular premolars (507 first premolars and 493 second premolars) with completely developed roots. CBCT was performed to assess the shape of the roots and to classify the canal anatomy according to Vertucci's classification. The incidence and similarity of the left and right sides, as well as men and women, were investigated. The data were examined using the chi-square test. Results. Of the 507 mandibular first premolars analyzed, 484 (95.5%) had one root, whereas 23 (4.5%) had two roots. Of the 493 mandibular second premolars analyzed, 489 (99.2%) had one root, whereas four teeth had two roots (0.8%). There were no statistically significant variations in the number of roots identified across groups (p > 0.05). The most prevalent in mandibular first premolars was type I, accounting for 70.0% (n = 355) of the studied sample, followed by type II (14.2%, n = 72) and type IV (10.1%, n = 51). For mandibular second premolar, type I had the highest incidence (449 (91.1%)), followed by type II (5.7%, n = 28). Conclusion. In a Saudi subpopulation, the majority of mandibular first and second premolar teeth had a single root with a type I canal system. On the other hand, numerous roots with various canal classifications were found.